2011
DOI: 10.1258/jtt.2010.100317
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of telerehabilitation at home after shoulder joint replacement

Abstract: We investigated the experience of ten patients who received video-based physiotherapy at home for two months after a shoulder joint replacement. Videoconferencing took place via the patient's home broadband connection at a bandwidth of 256-768 kbit/s. Qualitative interviews were carried out, transcribed and analysed. Through qualitative content analysis six categories were identified: (1) a different reinforced communication; (2) pain-free exercising as an effective routine; (3) from a dependent patient to a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
108
2
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 35 publications
9
108
2
8
Order By: Relevance
“…[4][5][6][7][8] Studies of video visits have demonstrated these benefits in specialty settings including wound care, prenatal genetic screening, family planning, cardiovascular care, and home care. [9][10][11][12][13][14][15] One study of patient experiences with video visits in rural areas found that they were associated with decreased travel costs and lost time/wages, increased access to social support, and better ability to tailor care delivery to patient and family needs. 16 Because of these benefits, video visits are being adopted in a variety of settings.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] Studies of video visits have demonstrated these benefits in specialty settings including wound care, prenatal genetic screening, family planning, cardiovascular care, and home care. [9][10][11][12][13][14][15] One study of patient experiences with video visits in rural areas found that they were associated with decreased travel costs and lost time/wages, increased access to social support, and better ability to tailor care delivery to patient and family needs. 16 Because of these benefits, video visits are being adopted in a variety of settings.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the home intervention, the physiotherapist's role relates to the the assessment, prevention and intervention, detecting compensatory mechanisms or ergonomic aspects to the patient, family and carers in their context (Von Koch et al, 1998 Regarding users of home physiotherapy the elderly are the main -though not the onlybeneficiaries, although changes in epidemiological patterns and the possibilities of technology transfer widen the availability of home physiotherapy (Elkan et al, 2001;Eriksson et al, 2010). Literature refers research studies and experiences in home physiotherapy envolving patients with diverse diagnosis.…”
Section: Home Physiotherapymentioning
confidence: 99%
“…In the healthcare domain, monitoring of a patient's recuperation from a Cerebrovascular Accident (CVA) or stroke has been shown to increase the effectiveness of rehabilitative interventions [1], [2]. The study in [3] considered the use of kinematic data -i.e.…”
Section: Introductionmentioning
confidence: 99%